2015
DOI: 10.5194/hess-19-1871-2015
|View full text |Cite
|
Sign up to set email alerts
|

Detecting groundwater discharge dynamics from point-to-catchment scale in a lowland stream: combining hydraulic and tracer methods

Abstract: Abstract. Detecting, quantifying and understanding groundwater discharge to streams are crucial for the assessment of water, nutrient and contaminant exchange at the groundwater-surface water interface. In lowland agricultural catchments with significant groundwater discharge this is of particular importance because of the risk of excess leaching of nutrients to streams. Here we aim to combine hydraulic and tracer methods from point-to-catchment scale to assess the temporal and spatial variability of groundwat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 66 publications
2
36
2
1
Order By: Relevance
“…As a sedimentation/scouring constraint, streambed elevation changes at the potential high‐discharge locations could not exceed ±0.05 m compared with the initial elevation of 13 October 2011 to exclude the effects of sedimentation and scouring in the data interpretation. Being a groundwater‐fed stream with groundwater discharge of variable upward fluxes (Karan et al ., ) everywhere along the stream channel (Poulsen et al ., ), the potential high‐discharge sites identified by this set of metrics and constraints indicate locations of potential high‐groundwater discharge as opposed to the diffuse discharge through the rest of the channel.…”
Section: Methodssupporting
confidence: 57%
“…As a sedimentation/scouring constraint, streambed elevation changes at the potential high‐discharge locations could not exceed ±0.05 m compared with the initial elevation of 13 October 2011 to exclude the effects of sedimentation and scouring in the data interpretation. Being a groundwater‐fed stream with groundwater discharge of variable upward fluxes (Karan et al ., ) everywhere along the stream channel (Poulsen et al ., ), the potential high‐discharge sites identified by this set of metrics and constraints indicate locations of potential high‐groundwater discharge as opposed to the diffuse discharge through the rest of the channel.…”
Section: Methodssupporting
confidence: 57%
“…This would decrease the calculated flow accretion at 04. It is shown that there is substantial difference in spatial and temporal groundwater seepage both across‐ and along the stream (Karan et al ; Poulsen et al ). Therefore, because the flux is calculated from a synchronous campaign, it is also likely that the vertical flux does not coincide with long‐term temperature monitoring trends at the site.…”
Section: Discussionmentioning
confidence: 99%
“…We measured high 3.0 L min −1 flux PFP seeps with a seepage meter. Despite the very few locations of PFPs, their high fluxes have the potential to contribute significantly to the groundwater gain across the site (Poulsen et al, 2015). The peat thickness map (Fig.…”
Section: Thermal Evaluation Of Groundwater Seepagementioning
confidence: 99%